The role of earthquakes and storms in the fluvial export of terrestrial organic carbon along the eastern margin of the Tibetan plateau: A biomarker perspective - Wang, Jin; Ma, Tian; Zhang, Fei; Hilton, Robert G.; Feng, Xiaojuan; Jin, Zhangdong (Frontiers in Earth Science, 2023)
Driven by earthquakes and intense rainfall, steep tectonically active mountains are hotspots of terrestrial organic carbon mobilization from soils, rocks, and vegetation by landslides into rivers. Subsequent delivery and fluvial mobilization of organic carbon from different sources can impact atmospheric CO2 concentrations across a range of timescales. Extreme landslide triggering events can provide insight on processes and rates of carbon export. Here we used suspended sediment collected from 2005 to 2012 at the upper Min Jiang, a main tributary of the Yangtze River on the eastern margin of the Tibetan Plateau, to compare the erosion of terrestrial organic carbon before and after the 2008 Wenchuan Earthquake and a storm-derived debris flow event in 2005. To constrain the source of riverine particulate organic carbon (POC), we quantified lignin phenols and n-alkanoic acids in the suspended sediments, catchment soils and landslide deposits. We found that riverine POC had higher inputs of less-degraded, discrete organic matter at high suspended sediment loads, while the source of POC seemed stochastic at low suspended sediment concentrations. The debris flow in 2005 mobilized a large amount of POC, resulting in an export of lignin within a single day equivalent to a normal year. In comparison, the 2008 Wenchuan earthquake increased the flux of POC and particulate lignin, albeit with limited impact on POC sources in comparison to seasonal variations. Our results highlight the important role of episodic events in the fluvial export of terrestrial carbon.